Evaluation of the P Wave Axis in Patients With Systemic Lupus Erythematosus - Rezzan Deniz Acar; Mustafa Bulut; Sencan Acar; Servet Izci; Serdar Fidan; Mahmut Yesin; Suleyman Cagan Efe (Journal of Cardiovascular and Thoracic Research, 2015)
Introduction: P wave axis is one of the most practical clinical tool for evaluation of cardiovascular disease. The aim of our study was to evaluate the P wave axis in electrocardiogram (ECG), left atrial function and association between the disease activity score in patients with systemic lupus erythematosus (SLE). Methods: Standard 12-lead surface ECGs were recorded by at a paper speed of 25 m/s and an amplifier gain of 10 mm/mV. The heart rate (HR), the duration of PR, QRS, QTd (dispersion), the axis of P wave were measured by ECG machine automatically. Results: The P wave axis was significantly increased in patients with SLE (49 ± 20 vs. 40 ± 18, P=0.037) and the disease activity score was found positively correlated with P wave axis (r: 0.382, P=0.011). The LA volume and the peak systolic strain of the left atrium (LA) were statistically different between the groups (P=0.024 and P=0.000). The parameters of the diastolic function; E/A and E/e’ were better in the control group than the patients with SLE (1.1 ± 0.3 vs. 1.3 ± 0.3, P=0.041 and 6.6 ± 2.8 vs. 5.4 ± 1.4, P=0.036, respectively). Conclusion: P wave axis was found significantly increased in patients with SLE and positively correlated with SELENA-SLEDAI score. As the risk score increases in patients with SLE, P wave axis changes which may predict the risk of all-cause and cardiovascular mortality.